"INNOVATIVE APPROACHES: CRAFTING EFFECTIVE METHODOLOGIES FOR TEACHING QUANTITIES IN ELEMENTARY MATHEMATICS" - Abdulazizova Fotima Azayumjon qizi (Western European Studies, 2024)
Students are introduced to the basic idea of quantities in elementary school, which lays the groundwork for a solid mathematics education. Creating efficient teaching strategies for quantities is essential to establishing the foundation for increasingly complex mathematical ideas. In order to provide students a better grasp and appreciation of numbers, we will look at creative ways to develop a solid technique for teaching amounts in primary mathematics classes in this article
Keywords: Activities; quantities; number; value